Memanfaatkan Hasil Asesmen Kompetensi Minimum (AKM) untuk Mendesain Multimodal Learning Aqidah Akhlak di MTs Hidayaturrahman NW Menggala - Sahari, Sahari (Jurnal Paedagogy, 2021)
This study aims to describe the design of Aqidah Akhlak multimodal learning at MTs Hidayaturrahman NW Menggala by utilizing the results of the minimum competency assessment (AKM). This research method uses a literature study with references to the material and articles analyzed from Google Scholar and books. The process of analyzing the data is qualitative. The results of this literature study explain that AKM results can capture the real condition of students in mastering the most basic competencies, namely reading literacy and numeracy literacy. These results can be used by teachers to improve and improve the quality of learning in the classroom. To carry out learning in the classroom, teachers need a certain approach. One approach that is considered quite effective to improve learning outcomes is a multimodal approach that leads to the multimodal learning of Akhlakul Karimah. The Akhlakul karimah multi-modal learning design was prepared by the teacher by utilizing the results of the AKM, namely groups of students who needed special, basic, skilled, and proficient interventions. Meanwhile, the designs that can be used are educational games, think-pair-share, case-based learning, personal journal entries, and multimodal research projects.